Pelatihan Penyusunan Perangkat Ajar Bermuatan Kearifan Lokal untuk Meningkatkan Kontekstualisasi Pembelajaran di Sekolah Dasar - Habibi Musa; Rista Apriliya Devi (Prodi PGSD Unsultra, 2025)
This community service activity aims to improve the capacity of Elementary School (SD) teachers in compiling teaching materials containing local wisdom as an effort to contextualize learning. The background of this activity is the low integration of local values ​​in the learning process which causes a lack of relevance of teaching materials to the environment of students. This training was carried out at GMIT Kuanino 1 Elementary School, Kupang City, which has a wealth of local culture such as the tradition of ikat weaving, folklore, and the values ​​of the lives of the people of East Nusa Tenggara. The method of implementing the activity consists of the stages of socialization, training, mentoring, and evaluation. The training materials include identification of local potential, techniques for integrating local wisdom into lesson plans and teaching modules, and the practice of compiling teaching materials based on the Merdeka Curriculum. The results of the activity showed an increase in teachers' understanding of the importance of local wisdom in learning and their ability to compile contextual teaching materials. Thus, this training makes a positive contribution to strengthening local cultural identity in education and increasing student involvement in the learning process. This activity also encourages teachers to become agents of cultural preservation through educational activities that are relevant to students' daily lives.